A Feasibility study on Rice strawboard panels - Castillo, Kermin Amor T.; Delos Santos, Jake C.; Salazar, Michelle Aileen S.; Santos, Patricia D. (College of Engineering, 1996)
The project is feasibility study on the production of Rice Strawboard Panels in Bulacan. The firm will be formed as a corporation and named Duraboard Enterprises, Incorporated. The product, rice strawboard panels, will mainly be made up of dry rice straw which is a waste material. It will be sourced from the rice farmers in Bulacan. The target market for the project is the low-cost housing industry in Metro Manila, Region III and Region IV and its demand for panelling. The government is currently undertaking a National Shelter Program (NSP). The NSP is a comprehensive program designed to provide affordable housing for the Filipino people. The government target is approximately 1.2 million houses by the year 1998. According to the survey , the project will capture 23.65% of this demand for panelling. The competitive price of the product is set at P200.00 per square meter. The company will undertake an aggressive marketing campaign in order to promote this new, indigenous product. Sale of the Rice Strawboard Panels are projected to amount to P60,480,000.00 in the first year and increasing by 5% annually. The initial capital outlay of the project is P114,000,000.00 which will cover the initial costs, working capital for three months, and a 10% contingency cost, Seventy percent (70%) of this amount will be loaned from the Development Bank of the Philippines at 12% interest compounded semi-annually for ten years. thirty percent (30%) of the project cost which amounts to P34,200,000.00 will be put up by private investors and shareholders. Evaluation of the company's financial position showed that the project will be very liquid, enough to meet its short-term debt. Net income for the first year amounts to P4,053,973.00. This amount increases each year. Asset turnover is within acceptable range indicating that assets are being used efficiently. Return on Assets in years two to five are always greater than 22% indicating that there is sufficient profit margin on sales. The Internal Rate of Return of 39.34% is greater than the acceptable rate of 15% making the project desirable. Payback period for the project is approximately three years. The establishment of Duraboard Enterprises will generate income and employment for the residents of Bulacan. The company will employ 57 personnel as soon as the plant is operational. The use of rice straw as a raw material will also generate added income for the rice farmers of Bulacan. The enterprise therefore will benefit the community and the country.